Parkinson's Disease Management Through ICT : The REMPARK Approach. - Cabestany, Joan. (River Publishers, 2017)
Parkinson's Disease Management through ICT: The REMPARK Approach presents the work done, main results and conclusions of the REMPARK project (2011 - 2015) funded by the European Union under contract FP7-ICT-2011-7-287677.